NEUROLINGUISTIC PROGRAMMING (NLP) IS A MODELING, ACTION, AND EFFECTIVE COMMUNICATION - Vazirakhon Rustamovna Ochilova (Western European Studies, 2024)
The article discusses the possibility of applying neuro-linguistic programming (NLP) to teaching English. Neuro-Linguistic Programming is referred to as NLP. These are systems theory in cybernetics, transformational grammar in linguistics, and neuroscience. The recommended strategies and approaches are listed, along with the advantages and disadvantages of each. Since learning a foreign language is a difficult and complex talent, it must be modeled by dividing it down into multiple related abilities. Using NLP technologies, you may uncover a number of intriguing aspects that are frequently hidden from English language teachers. They consist of nonverbal responses, anchor acts, behavioral patterns, underlying presumptions, strategies, and eye movements, among other things. One can imitate learning a language
Keywords: neuro-linguistic programming; environment; abilities